CHARACTERISTICS OF MOTIVATION OF STUDENTS TO LEARNING - Radjabova Gavkhar Umarovna; Madaminova Mohimbonu (Galaxy International Interdisciplinary Research Journal, 2022)
The article analyzes the peculiarities of students’ motivation in higher educational institutions. The features of motivation on the part of both teachers of higher educational institutions and the features of motivation on the part of the students themselves are considered, taking into account the individual characteristics of each individual student.